Interplay between epigenetics and metabolism controls cancer stem cell plasticity - Choi, Jee-Eun; Baek, Inwha (Frontiers in Epigenetics and Epigenomics, 2024)
Tumors consist of cancer cells with different genetic, epigenetic, and phenotypic properties. Cancer stem cells are an important subpopulation of heterogeneous cancer cells and are capable of initiating and propagating tumors. The term cancer stem cells has become broader in efforts to understand their phenotypic plasticity to switch fates between self-renewal and differentiation. Cancer stem cell plasticity is significantly associated with the initiation of metastasis, resistance to therapy, and tumor recurrence. With our broadened knowledge of epigenetic regulation and metabolic reprogramming as key elements enabling such capabilities, an expansive body of literature has demonstrated the functional importance of each element in contributing to cancer stem cell characteristics. Recently, the direct interplay between epigenetic regulation and metabolic reprogramming has begun to be appreciated in the context of cancer stem cells with growing interest. In this review, we discuss the mechanisms by which cancer stem cells orchestrate the reciprocal regulation of cellular metabolism and epigenetic alterations. In the discussion, compelling, unanswered questions on this topic have been elaborated for the interest of the research community and how recent technological developments help tackle such research ideas. A comprehensive understanding of cancer stem cell attributes that are largely governed by epigenetic and metabolic reprogramming would enable the advancement of precise therapeutic options and the prediction of better responses to drugs, holding great promise in cancer treatment and cure.